2019
DOI: 10.1111/jnc.14883
|View full text |Cite
|
Sign up to set email alerts
|

Targeting aurora kinase B alleviates spinal microgliosis and neuropathic pain in a rat model of peripheral nerve injury

Abstract: Peripheral nerve injury elicits spinal microgliosis, contributing to neuropathic pain. The aurora kinases A (AURKA), B (AURKB), and C (AURKC) are potential therapeutic targets in proliferating cells. However, their role has not been clarified in microglia. The aim of this study was to examine the regulation of aurora kinases and their roles and druggability in spinal microgliosis and neuropathic pain. Sprague–Dawley rats received chronic constriction injury (CCI). Gene expression of aurora kinases A‐C was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…In the spinal cord, microglia respond to a peripheral nerve injury by producing inflammatory mediators, which lead to neuronal hyper-excitability and central sensitization (Gu et al, 2016;Donatien et al, 2018;Shen et al, 2020). The reactive microglia participating in the neuroinflammation are classified into two main states of activation: the M1 phenotype characterized by secretion of pro-inflammatory factors, and the alternative anti-inflammatory M2 phenotype involved in the resolution of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In the spinal cord, microglia respond to a peripheral nerve injury by producing inflammatory mediators, which lead to neuronal hyper-excitability and central sensitization (Gu et al, 2016;Donatien et al, 2018;Shen et al, 2020). The reactive microglia participating in the neuroinflammation are classified into two main states of activation: the M1 phenotype characterized by secretion of pro-inflammatory factors, and the alternative anti-inflammatory M2 phenotype involved in the resolution of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…All the assessment were carried out after the rats were acclimated in specific individual chambers at least 30 min. The PWMT was measured with Von Frey filaments (North Coast Medical, San Jose, CA, 11 USA) ranging from 0.4g-15g, as described in our previous study 23,24 . Briefly, the stimuli were applied vertically to the plantar surface of the left hind paw, and the minimal force that could cause three consistent withdrawal responses (lifting or licking) was considered as the PWMT.…”
Section: 3behavioral Assessmentmentioning
confidence: 99%
“…Briefly, the stimuli were applied vertically to the plantar surface of the left hind paw, and the minimal force that could cause three consistent withdrawal responses (lifting or licking) was considered as the PWMT. A thermal pain test instrument (Tes7370, Ugo Basile, Comerio, Italy) 23,24 was used for the test of PTWL. In a brief, after the rats were habituated in the cage for 30 min, a continuous heat stimuli was applied to their plantar surface of hindpaw to evoke withdrawal responses and meanwhile the timer recorded the latency.…”
Section: 3behavioral Assessmentmentioning
confidence: 99%
“…It has become a public health problem worldwide due to the long course of the disease, its high incidence, and its tendency to markedly reduce patients' quality of life [ 2 ]. However, there are currently no satisfactory treatments for neuropathic pain [ 3 ]. Thus, exploring the mechanism of neuropathic pain to provide novel insight into and a basis for the treatment of pain is of importance.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are endogenous, noncoding RNA with approximately 22 nucleotides in length that are found widely in eukaryotes and prevent mRNA translation and/or promote protein degradation by complementarily binding to specific sites in the 3′-untranslated regions (3′-UTRs) of target genes [ 4 ]. Some studies have demonstrated that miRNAs are related to the process of chronic pain (Qiang [ 3 , 18 ]) and that EA might enhance the repair of peripheral nerve injury (PNI) through regulating miRNAs [ 13 ]. Evidence has suggested that an increase in miR-206 expression aids the recovery from neuropathic pain [ 15 ].…”
Section: Introductionmentioning
confidence: 99%